Inisiasi Produksi Massal Körperkoordinationstest für Kinder Jumping Sideway Digital Counter - Romi Mardela; Syahrial Bakhtiar (Jurnal Berkarya Pengabdian Masyarakat, 2022)
"KTK Jumping Sideway Digital Counter" is a modified digital-based test instrument that has been tested for validity and reliability, which aims to measure motor coordination and agility. Making “KTK Jumping Sideway Digital Counter” using low-cost technology components for mass-produced to reduce production costs. In order to achieve this target, it requires Physical Education teachers at the elementary school level to be able pioneering for the mass-production of this instrument test. It is important to start produced and implemented at the elementary school level as well as to assess the effectiveness and efficiency mass-produced of this KTK Jumping Sideway digital counter.